URBAN GARDENS – SPACES FOR RECOVERY AND ELEMENTS OF THE SUSTAINABLE DEVELOPMENT CONCEPT - Tsepur, Yelyzaveta; Kosyk, Oksana (Theory and practice of design, 2025)
The article explores the role of urban gardens as therapeutic, social, and ecological spaces within contemporary urban environments. The study examines how green areas contribute to improving psychophysical health, reducing stress, strengthening social interaction, and enhancing ecological stability in cities. Special attention is given to therapeutic and inclusive gardens, as well as international and Ukrainian practices of their implementation. Purpose. The purpose of the study is to identify the therapeutic and social potential of urban gardens, substantiate their role in restoring psychophysical wellbeing, and justify the importance of integrating green spaces into modern urban infrastructure. Methodology. A comprehensive methodological approach was applied, including the analysis of scientific literature on urban ecology, landscape architecture, and psychoecology; a comparative-analytical method to assess international and national examples of therapeutic gardens; a structural–functional analysis to determine the role of plant compositions and spatial organization in producing restorative effects; and a project-modelling approach for evaluating compositional and sensory solutions in inclusive green spaces. Empirical observations of implemented projects were used to assess their ecological, psychological, and social efficiency. Results. The study established that urban gardens significantly contribute to reducing stress levels, improving emotional well-being, and fostering social cohesion. Green spaces enhance air quality, regulate microclimate, and support urban biodiversity. Therapeutic gardens, community gardens, and inclusive green zones demonstrate high potential for facilitating rehabilitation, especially for vulnerable groups such as children, the elderly, veterans, and people with disabilities. Their integration into urban planning strengthens resilience and promotes healthier, more sustainable cities. Scientific novelty. For the first time, the study synthesizes interdisciplinary approaches to understanding urban gardens as multifunctional restorative systems that combine ecological value, therapeutic potential, and social integration. It clarifies the classification of urban garden functions and defines the conceptual framework for designing inclusive and sensory-based therapeutic spaces. Practical relevance. The findings can be applied in designing therapeutic and recreational gardens, planning green infrastructure for medical and rehabilitation facilities, and developing inclusive public spaces. The recommendations support the creation of environmentally sustainable, socially engaging, and health-promoting urban environments, contributing to post-war recovery and long-term urban resilience.